1973
DOI: 10.1128/iai.7.3.373-379.1973
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Virulence of Neisseria gonorrhoeae I. Relation of Colonial Morphology and Resistance to Phagocytosis by Polymorphonuclear Leukocytes

Abstract: Colonial varieties of Neisseria gonorrhoeae that are associated with virulence, types 1 and 2, were more resistant to phagocytosis by rabbit exudative polymorphonuclear leukocytes than colonial, types of lesser virulence, types 3 and 4. Type 1 bacteria were resistant and type 4 gonococci were susceptible to phagocytosis by human polymorphonuclear leukocytes. Recent local type 1 isolates were similar in resistance to type 1 organisms of a standard laboratory strain (F62). Living and Formalin-treated, heat-kille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 10 publications
4
69
2
Order By: Relevance
“…The interaction between types of N. gonorrhoeae and human sperm were similar to those reported for other eukaryotic cells (9,13,14). In all of these studies, piliated bacteria of type 1 attached to cells to a greater degree than nonpiliated type 4 bacteria.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The interaction between types of N. gonorrhoeae and human sperm were similar to those reported for other eukaryotic cells (9,13,14). In all of these studies, piliated bacteria of type 1 attached to cells to a greater degree than nonpiliated type 4 bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…Microbiol., p. 126, 1973) related a specific surface characteristic of the gonococcus to virulence. One laboratory reported that pili both promoted adherence of gonococci to eukaryotic cells and reduced phagocytosis of the bacteria (9,14).…”
mentioning
confidence: 99%
“…Moreover, piliated gonococci unable to undergo phase variation due to a deletion in the recA locus, were about two orders of magnitude less invasive than their nonpiliated counterparts. This brings to mind previous data suggesting that pili elicit antiphagocytic effects (Punsalang and Sawyer, 1973;Thongthai and Sawyer, 1973;Ofek et al, 1974;Densen and Mandell, 1978), although this notion has not been confirmed by others (Virji and Heckels, 1986). Whether the inhibitory effect of piliation is influenced by the particular type of pilin variant studied (i.e.…”
Section: Discussionmentioning
confidence: 84%
“…However, some strains subsequently agglutinated when incubated in 10% fresh normal human serum for 60 min ; these strains were omitted from phagocytosis studies . Previous studies of gonococci have employed stained smears for evaluation of phagocytosis (4)(5)(6) . Fresh serum was also omitted from these studies.…”
Section: Stability Of Colonial Typesmentioning
confidence: 99%
“…Nonselective transfer of type 1 and 2 gonococci on artificial medium resulted in reversion to type 3 and 4 organisms (2,3) . Recent morphologic studies have suggested that colonial types 1 and 2 gonococci are more resistant to phagocytosis than type 3 and 4 organisms (4)(5)(6) .…”
mentioning
confidence: 99%